Implementation and Effectiveness of GIS-Based Projects in Secondary Schools - ÜNLÜ, MEHMET (TAYLOR & FRANCIS INC, 2013)
This study aims to provide an understanding of the main obstacles to conducting GIS-based projects in secondary schools and to determine the effects of these projects on students, teachers, and schools. The study was conducted in three public high schools in Turkey. The students first surveyed over 4,015 people in their school districts to understand the main social, environ- mental, and economic problems in their area, then conducted nine different GIS-based projects to help design solutions to these problems. As seen in the study, GIS is a very important teaching and learning tool for secondary schools; however, its effective use depends on planning, motivation, support, resources, time, and enthusiasm, especially for teachers.
Keywords: GIS-based projects; project-based learning; secondary schools; geography education; Turkey; LEARNING-ENVIRONMENT; EDUCATION; STUDENTS; GEOGRAPHY